Educational Software as a Support for Teaching in Programming - Briones, Servando Campillay; Guggiana Diaz, Carlo (2018 37th International Conference of the Chilean Computer Science Society (SCCC), 2018)
The present article shows the process of development and incorporation of an educational software in the teaching of the subject of Introduction to Programming included in the Common Plan of the Faculty of Engineering of the University of Atacama, which is considered a critical subject (with Low approval levels), its main objective is to facilitate learning in problem solving using concepts, methods and work paradigms based on the contents of the current curriculum. Within the obtained results it is possible to emphasize the improvement in the understanding of the contents in the subject, which requires a logical thinking and understanding of the problem, considering that its resolution can be approached in multiple ways. Another result observed is the increase in the approval rate, achieving an increase of 25% compared to previous semesters.